2016
DOI: 10.1186/s12889-016-3657-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between workplace bullying and depressive symptoms: the role of the perpetrator

Abstract: BackgroundThe aim of the present study was to investigate whether the depressive symptoms of the bullied respondents differed according to who the perpetrator was.MethodsWe used cross-sectional questionnaire data from two representative cohorts: the Danish Working Environment Cohort Study (DWECS 2010) and the Work and Health Study (WH 2012). After excluding respondents not having a leader, or being self-employed, assisting spouses, and those reporting multiple perpetrators in WH 2012, the statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
2
15
1
Order By: Relevance
“…A crucial difference is that PSC is also expected to affect work design and leadership aspects that could affect bullying. This difference is important given that, consistent with much of the literature, particularly from the UK, US, and Europe but less so in Scandinavian countries (Török et al, 2016), we found that most cases of bullying, nearly 70%, were perpetrated by a supervisor. This finding implies that the vanguard of organizational PSC climate, the leaders themselves, need professional training and development in job design, ethical leadershiphow to carry out managerial functions whilst ensuring fair treatmentand training in the development of conflict resolution processes, to provide an optimal work climate.…”
Section: Practical Implicationssupporting
confidence: 82%
“…A crucial difference is that PSC is also expected to affect work design and leadership aspects that could affect bullying. This difference is important given that, consistent with much of the literature, particularly from the UK, US, and Europe but less so in Scandinavian countries (Török et al, 2016), we found that most cases of bullying, nearly 70%, were perpetrated by a supervisor. This finding implies that the vanguard of organizational PSC climate, the leaders themselves, need professional training and development in job design, ethical leadershiphow to carry out managerial functions whilst ensuring fair treatmentand training in the development of conflict resolution processes, to provide an optimal work climate.…”
Section: Practical Implicationssupporting
confidence: 82%
“…In a 2018 survey about workplace violence administered to health management experts in China, the overall prevalence was 62.4% [14]. In a representative survey of working environments in Denmark, around 12% of respondents were exposed to workplace harassment [3], and 2.2% reported unwanted sexual attention [15]. This was similar to the results of the 2016 KWCS, which reported the prevalence of workplace violence in South Korea as 6.0% [6].…”
Section: Discussionsupporting
confidence: 58%
“…Workplace violence has become an important public health issue in many countries, and its relationship to employee health has become a trending research topic [2]. The prevalence of workplace violence varies depending on the conceptual definition, workplace culture, work characteristics, and national labor policies [3]. Decreasing trends in workplace violence have been reported in the US [4], but studies on Europe have found it is increasing [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable that the negative effect of exposure to bullying behaviours may be different depending on if the source is some or all of your co-workers, your supervisor, a client, or a combination of several sources. For example, Törek et al (2016) showed that employees exposed to workplace bullying from leaders experienced more severe depressive symptoms compared to those that were bullied by co-workers or clients. This result somehow contradicts the reasoning connected to social exchange theory (above) where, for example, proximity (Svensson 2010) and the quality of relationships (Wanous 1992) were of particular importance.…”
Section: Discussionmentioning
confidence: 99%